Antimikroba: Magic Bullet Versus Superbugs - Silvia Sutandhio; Lindawati Alimsardjono; Eddy Bagus Wasito (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2018)
Magic bullet is a terminology used by Paul Ehrlich to refer to substance that selectively attacks microbes that cause infection without affecting human tissues. The concept of magic bullet is adopted in attempts to find antimicrobial drugs that is safe to human. Improper and excessive use of antimicrobial drugs has caused the emergence ofmicrobes that are resistant to various antimicrobial drugs (superbugs). Superbugs are recent healthcare and public health issues. This condition is exacerbated bythe discovery void of effective antimicrobial drug against superbugs. Health practitioners must perform prudent use of antibiotics in order to prevent transmission of and infection by superbugs.